2013
DOI: 10.1002/jts.21777
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic Stress Disorder, Depression, and HIV Risk Behavior Among Ohio Army National Guard Soldiers

Abstract: We examined the relationship between posttraumatic stress disorder (PTSD), major depressive disorder (MDD), and human immunodeficiency virus (HIV) risk behavior among the Ohio Army National Guard (OHARNG). We analyzed data collected from a sample of OHARNG enlisted between June 2008 and February 2009. Participants completed interviews assessing HIV risk activities defined by the Behavioral Risk Factor Surveillance System, and were screened for PTSD and MDD based on DSM-IV criteria according to the Diagnostic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 55 publications
(55 reference statements)
2
13
0
2
Order By: Relevance
“…The overall response rate was 43.2%; calculated as the number of participants who completed a survey and consented but were ineligible divided by the number of working numbers minus those that were disqualified (2616+187/6514-31). Additional details about participant sampling and recruitment are available elsewhere (see Biehn et al, 2012; Calabrese et al, 2011; Goldmann et al, 2012; Goodwin et al, 2012; 2013; Marshall et al, 2012; 2013). …”
Section: Methodsmentioning
confidence: 99%
“…The overall response rate was 43.2%; calculated as the number of participants who completed a survey and consented but were ineligible divided by the number of working numbers minus those that were disqualified (2616+187/6514-31). Additional details about participant sampling and recruitment are available elsewhere (see Biehn et al, 2012; Calabrese et al, 2011; Goldmann et al, 2012; Goodwin et al, 2012; 2013; Marshall et al, 2012; 2013). …”
Section: Methodsmentioning
confidence: 99%
“…8 In a study of 400 male and female patients attending an outpatient psychiatry clinic, more than half did not use a condom at the last five sex acts and almost 25% reported binge drinking in the past 30 days. 9 Specifically, women with chronic mental illness may be more vulnerable to coerced sex and have higher levels of sexual impulsivity.…”
Section: Introductionmentioning
confidence: 99%
“…This finding was somewhat unexpected since prior research has found traumatic events, such as peer sexual coercion, to be associated with increased risky sexual behavior in adolescence (Young, Furman, & Jones, 2012). However, other studies have shown no association between PTSD and sexual HIV risk behaviors (Stiffman et al, 1992; Marshall et al, 2013) among adults. It may be that PTSD confers risk for sexual activity in the context of interpersonal trauma rather than other forms of trauma.…”
Section: Discussionmentioning
confidence: 83%